Clinical Management of Potential Toxicities and Drug Interactions Related to Cyclin‐Dependent Kinase 4/6 Inhibitors in Breast Cancer: Practical Considerations and Recommendations. (September 2017) - Spring, Laura M.; Zangardi, Mark L.; Moy, Beverly; Bardia, Aditya
Abstract: Aberrations of the cell cycle are pervasive in cancer, and selective cell cycle inhibition of cancer cells is a target of choice for a number of novel cancer therapeutics. Cyclin‐dependent kinases (CDKs) are key regulatory enzymes that control cell cycle transitions and the commitment to cell division. Palbociclib and ribociclib are both orally active, highly selective reversible inhibitors of CDK4 and CDK6 that are approved by the U.S. Food and Drug Administration (FDA) for hormone receptor‐positive metastatic breast cancer in combination with specific endocrine therapies. A third oral CDK4/6 inhibitor, abemaciclib, received Breakthrough Therapy designation status from the FDA and is also being developed in breast cancer. The most common adverse events associated with palbociclib and ribociclib are hematologic, particularly neutropenia. However, the neutropenia associated with CDK4/6 inhibitors is distinct from chemotherapy‐induced neutropenia in that it is rapidly reversible, reflecting a cytostatic effect on neutrophil precursors in the bone marrow. Most hematologic abnormalities seen with CDK4/6 inhibitors are not complicated and are adequately managed with standard supportive care and dose adjustments when indicated. Cytopenias are less prevalent with abemaciclib, although fatigue and gastrointestinal toxicity is more common with this agent. This review focuses on the clinical management of potential toxicities and drug interactions seen with the use of CDK4/6 inhibitors in breast cancer, with a focus on palbociclib and ribociclib, and summarizes practical management strategies for an oncologist. Implications for Practice: The emergence of modern cyclin‐dependent kinase (CDK) inhibitors has changed the treatment paradigm for metastatic hormone receptor (HR)‐positive breast cancer. Palbociclib, ribociclib, and abemaciclib are highly selective reversible inhibitors of CDK4 and CDK6. Palbociclib is U.S. Food and Drug Administration (FDA)‐approved in the first‐ and second‐line settings in combination with endocrine therapy for HR‐positive metastatic breast cancer. Ribociclib is FDA‐approved in the first‐line setting. Abemaciclib has received FDA Breakthrough Therapy designation status. This review focuses on the clinical management of potential toxicities and drug interactions seen with the use of CDK4/6 inhibitors in breast cancer. Abstract : This review article reports the clinical management of potential toxicities and drug interactions seen with the use of CDK4/6 inhibitors in breast cancer, with a focus on palbociclib and ribociclib, and summarizes practical management strategies for the oncologist.